Analisis Penentuan Pusat-Pusat Pertumbuhan Ekonomi di Kabupaten Siak - Prisa, Prisa Putri Neysa; Hamidi, Wahyu; desweni, selly prima (Indonesian Journal Publisher, 2024)
This study aims to determine which sub-districts are the centers of economic growth in Siak Regency, as well as the interaction between the sub-districts of economic growth centers and sub-districts in the surrounding area. This research uses secondary data in 2023 sourced from BPS Riau Province, BPS Siak Regency, as well as journals and literacy related to this research. The data analysis method used in this research is Scalogram Analysis by combining the Centrality Index and weighting techniques and Gravity Analysis. Scalogram Analysis is used to determine the centers of economic growth in each sub- district based on the availability of public service facilities such as government facilities, economic facilities, and social facilities. Gravity Analysis is used to determine how much interaction between the center of economic growth subdistricts and the surrounding sub-districts (Hinterland) using the variables of population and distance between the two regions. Based on the research results from the Scalogram Analysis and Centrality Index that have been carried out, the growth center in Siak Regency based on 34 service facilities is Siak District with the highest total service facilities and Centrality Index. Based on the results of Gravity Analysis using population variables and the distance from the economic growth center sub-district to the surrounding area (Hinterland), it can be seen that the growth center sub-district of Siak District has the strongest interaction relationship with Tualang District as the surrounding area (Hinterland).